Opioid Risk Mitigation Strategies and Overdose Resuscitation - Martin Klapheke; Magdalena Pasarica (Association of American Medical Colleges, 2017)
Introduction In the context of an opioid public health crisis, U.S. medical schools have been called upon to strengthen curricula on the appropriate use of opioids, with an emphasis on maximizing benefits while utilizing risk-mitigation strategies to prevent addiction and overdose. Methods This self-contained module provides an overview of the opioid crisis and presents recent clinical guidelines on opioid risk mitigation, as well as information regarding prevention and treatment of opioid overdose. This module then gives learners the opportunity to practice these skills by solving an evolving case of back pain. Results Verbal and written feedback on the module from students revealed that the majority strongly agreed that, overall, the module was valuable as an educational tool. Discussion This module was created to help medical educators update the training of students in risk mitigation strategies and the steps of opioid overdose resuscitation. The feedback to date from students and faculty has been positive and supports its use in undergraduate medical education.